2008
DOI: 10.1097/jto.0b013e31818e1247
|View full text |Cite
|
Sign up to set email alerts
|

Primary Small Cell Carcinoma of the Esophagus

Abstract: SCEC is systemic disease. Tumor stage and chemotherapy were independent prognostic factors. Systemic therapy, based on chemotherapy with radiotherapy, is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
92
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 15 publications
11
92
4
Order By: Relevance
“…Small cell neuroendocrine carcinoma (SCNEC) is a rare disease with aggressive and malignant biological behavior and a poor prognosis. SCNEC accounts for 1.0 to 2.8% of all esophageal cancers (2,3). A new classification of neuroendocrine tumors that included SCNEC was introduced by the World Health Organization (WHO) in 2010 (4).…”
Section: Introductionmentioning
confidence: 99%
“…Small cell neuroendocrine carcinoma (SCNEC) is a rare disease with aggressive and malignant biological behavior and a poor prognosis. SCNEC accounts for 1.0 to 2.8% of all esophageal cancers (2,3). A new classification of neuroendocrine tumors that included SCNEC was introduced by the World Health Organization (WHO) in 2010 (4).…”
Section: Introductionmentioning
confidence: 99%
“…11 24 32 Some authors have recommended surgery for patients with LD, 8 and Lv, et al 2 reported MST analysis based on the therapeutic method. However, their conclusions were controversial, with Chen, et al reporting surgery with chemotherapy as an independent prognostic factor, 10 and Lv reporting chemotherapy as an independent prognostic factor.…”
Section: -3 8-9 13 16 19-20 21 24mentioning
confidence: 99%
“…However, their conclusions were controversial, with Chen, et al reporting surgery with chemotherapy as an independent prognostic factor, 10 and Lv reporting chemotherapy as an independent prognostic factor. 2 Multidrug combination chemotherapy seems effective with or without surgery. Vos reported that chemotherapy prolonged MST from 9.5 months (interquartile range [IQR], 6-14 months) to 6 months (IQR, 4-7 months) in ED, and concurrent CRT prolonged MST from 36 months (IQR, 14-93 months) to 11 months (IQR, 9-15 months) in LD compared with nonconcurrent chemotherapy and radiotherapy.…”
Section: -3 8-9 13 16 19-20 21 24mentioning
confidence: 99%
See 2 more Smart Citations